Notes on the status of some species of the Medetera jacula group (Diptera: Dolichopodidae) - Negrobov, Oleg P. (Zootaxa, 2010)
Currently, Grichanov (2002, 2007) placed in synonymy a number of species belonging to the Medetera jacula group, but without proper discussion based on the analysis of characters of the type specimens. In this paper arguments are provided in support for the re-establishment of these species.